Dari Akreditasi ke Mutu Layanan: Analisis Strategi Manajemen Program PAUD di Wilayah Parongpong, Kabupaten Bandung Barat - diantifani rizkita; Mohamad Heri Hadian (Jurnal Pendidikan UNIGA, 2026)
Accreditation is a national instrument used to assess the feasibility and quality of educational services, including Early Childhood Education (ECE). However, accreditation is often perceived as an end goal, whereas it should serve as an initial foundation for establishing sustainable quality management. This study aims to analyze post-accreditation program management strategies in ECE institutions located in Parongpong, West Bandung Regency. A qualitative approach with a case study design was employed, involving two accredited ECE institutions. Data were collected through in-depth interviews, observations, and document analysis, and were analyzed using the interactive model proposed by Miles and Huberman.The findings indicate that program management strategies focus on: (1) planning based on children’s needs, achievement evaluation, and community involvement; (2) implementation through collaboration with parents, partnerships with local stakeholders, and environmentally based learning innovations; and (3) continuous evaluation through internal supervision, joint monitoring with parents, and the use of simple digital instruments. Supporting factors include strong community support, trained teachers, and parental awareness, while inhibiting factors comprise limited funding, administrative workload, and variations in teachers’ commitment.This study concludes that accreditation should be viewed as a gateway to continuous service quality improvement, whose sustainability depends largely on adaptive, participatory, and innovative program management strategies.